Joyce Writing Disability - Linett, Maren Tova; Colangelo, Jeremy, 1990- (Book collections on Project MUSE., 2022)
"In this book, the first to explore the role of disability in the writings of James Joyce, contributors approach the subject both on a figurative level, as a symbol or metaphor in Joyce's work, and also as a physical reality for many of Joyce's characters. Contributors examine the varying ways in which Joyce's texts represent disability and the environmental conditions of his time that stigmatized, isolated, and othered individuals with disabilities.The collection demonstrates the centrality of the body and embodiment in Joyce's writings, from Dubliners and A Portrait of the Artist as a Young Man to Ulysses and Finnegans Wake. Essays address Joyce's engagement with paralysis, masculinity, childhood violence, trauma, disorderly eating, blindness, nineteenth-century theories of degeneration, and the concept of "madness."Together, the essays offer examples of Joyce's interest in the complexities of human existence and in challenging assumptions about bodily and mental norms. Complete with an introduction that summarizes key disability studies concepts and the current state of research on the subject in Joyce studies, this volume is a valuable resource for disability scholars interested in modernist literature and an ideal starting point for any Joycean new to the study of disability.A volume in the Florida James Joyce Series, edited by Sebastian D. G. Knowles"--